Hubungan kualitas tidur terhadap perolehan hasil ujian mahasiswa pre-klinis pendidikan dokter Fakultas Kedokteran Universitas Udayana - Kevin Kristian Putra; Made Dharmadi . (E-Jurnal Medika Udayana, 2018)
Sleep is essentially needed to people. The normal sleep period is 8 hours. In learning process, sleep quality is important in memory making process especially in consolidation process. Consolidation is a process to strengthen the new input memory to be long-term memory. This is an explorative descriptive research with cross-sectional study and correlation analysis. The samples are from second, fourth, and sixth semester of year 2014/2015 at medical faculty of Udayana University. Sleep quality is measured using the PSQI questionnaire (? = 0.83). Learning outcome is measured with the categorical data of the exam score based on the passing grade. From the research, students with good sleep quality have better amount of who pass the exam than poor sleep quality (pass: 63.7%; not pass: 36.3%). There is a very weak correlation between sleep quality and learning achievement (X2=0.196; P=0.000). It concludes that good sleep quality correlate with better learning achievement than poor sleep quality. Keywords: Sleep quality, exam result, PSQI, correlation